The Cancer Microenvironment: Mechanical Challenges of the Metastatic Cascade - Amos, Sebastian E.; Choi, Yu Suk (Frontiers in Bioengineering and Biotechnology, 2021)
The metastatic cascade presents a significant challenge to patient survival in the fight against cancer. As metastatic cells disseminate and colonize a secondary site, stepwise exposure to microenvironment-specific mechanical stimuli influences and protects successful metastasis. Following cancerous transformation and associated cell recruitment, the tumor microenvironment (TME) becomes a mechanically complex niche, owing to changes in extracellular matrix (ECM) stiffness and architecture. The ECM mechanically reprograms the cancer cell phenotype, priming cells for invasion. 2D and 3D hydrogel-based culture platforms approximate these environmental variables and permit investigations into tumor-dependent shifts in malignancy. Following TME modification, malignant cells must invade the local ECM, driven towards blood and lymph vessels by sensing biochemical and biophysical gradients. Microfluidic chips recreate cancer-modified ECM tracks, empowering studies into modes of confined motility. Intravasation and extravasation consist of complex cancer-endothelial interactions that modify an otherwise submicron-scale migration. Perfused microfluidic platforms facilitate the physiological culture of endothelial cells and thus enhance the translatability of basic research into metastatic transendothelial migration. These platforms also shed light on the poorly understood circulating tumor cell, which defies adherent cell norms by surviving the shear stress of blood flow and avoiding anoikis. Metastatic cancers possess the plasticity to adapt to new mechanical conditions, permitting their invasiveness and ensuring their survival against anomalous stimuli. Here, we review the cellular mechanics of metastasis in the context of current in vitro approaches. Advances that further expose the mechanisms underpinning the phenotypic fluidity of metastatic cancers remain central to the development of novel interventions targeting cancer.